1990
DOI: 10.2134/agronj1990.00021962008200060019x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato Root and Biomass Production with and without Nitrogen Fertilization

Abstract: Previous work suggests that some sweet potato (Ipomoea batatas, L.) cultivars can produce high storage root yields on soils without fertilizer N addition. This study was conducted to compare storage root yields, total biomass, N uptake and fibrous root weights of sweet potato cultivars grown on low N level soils with and without N addition. In 1987 and 1988, improved sweet potato cultivars developed at International Institute of Tropical Agriculture (liT A), Ibadan, Nigeria were grown with and without 50 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 4 publications
1
37
1
1
Order By: Relevance
“…Further studies are needed to determine if the endophytes might contribute to the N input in sweet potato plants that grow well in unfertile soil. Previous reports indicated that associative N 2 fixation contributes to the N uptake in sweet potato plants (Yoneyama et al 1998;Hill et al 1990). Nitrogen fixing endophytes like Azospirillum sp.…”
Section: Discussionmentioning
confidence: 98%
“…Further studies are needed to determine if the endophytes might contribute to the N input in sweet potato plants that grow well in unfertile soil. Previous reports indicated that associative N 2 fixation contributes to the N uptake in sweet potato plants (Yoneyama et al 1998;Hill et al 1990). Nitrogen fixing endophytes like Azospirillum sp.…”
Section: Discussionmentioning
confidence: 98%
“…Sweet potato has high N requirements but can produce reasonable yields in soils of poor fertility (Hill et al, 1990). This may be partly caused by its capacity to fix atmospheric N through association with symbiotic, non-nodulating bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The sweet potato (Ipomoea batatas L.) is known for its ability to grow well in nitrogen (N)-poor soils 16) . It is also known that the total amount of N in sweet potato exceeds the amount of N applied as chemical fertilizer.…”
mentioning
confidence: 99%